Gapped commensurate antiferromagnetic response in a strongly underdoped model cuprate superconductor - Z. W. Anderson; Y. Tang; V. Nagarajan; M. K. Chan; C. J. Dorow; G. Yu; D. L. Abernathy; A. D. Christianson; L. Mangin-Thro; P. Steffens; T. Sterling; D. Reznik; et al. (npj Quantum Materials)
Abstract It is a distinct possibility that spin fluctuations are the pairing interactions in numerous unconventional superconductors. In the high-transition-temperature (high-T c) cuprates, superconductivity emerges upon doping antiferromagnetic Mott insulators, and spin fluctuations might furthermore drive unusual pseudogap phenomena. Here we use magnetic neutron scattering to study the highly underdoped cuprate HgBa2CuO4+δ (hole concentration p ≈ 0.064). In contrast to prior results for other underdoped cuprates, we find no evidence of incommensurate magnetic order associated with spin-density-wave or stripe correlations. Instead, the antiferromagnetic response in both the superconducting and pseudogap states is gapped below ΔAF ≈ 6 meV, commensurate over a wide energy range, and disperses above about 55 meV. Given the pristine nature of HgBa2CuO4+δ , which exhibits high structural symmetry and minimal point disorder effects, this behavior likely signifies the unmasked response of the underlying CuO2 planes near the Mott-insulating state. These results serve as a benchmark for a refined theoretical understanding of the cuprates.